Organic redox systems : synthesis, properties, and applications - Nishinaga, Tohru (Hoboken, New Jersey : John Wiley & Sons, 2016)
Providing a thorough overview of leading research from internationally-recognized contributing authors, this book describes methods for the preparation and application of redox systems for organic electronic materials like transistors, photovoltaics, and batteries. - Covers bond formation and cleavage, supramolecular systems, molecular design, and synthesis and properties- Addresses preparative methods, unique structural features, physical properties, and material applications of redox active p-conjugated systems- Offers a useful guide for both academic and industrial chemists involved with organic electronic materials- Focuses on the transition-metal-free redox systems composed of organic and organo main group compounds.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Oxidation-reduction reaction; Oxidation-reduction reaction; SCIENCE / Chemistry / Organic; Electronic books